High Incidence of Somatic BAP1 Alterations in Sporadic Malignant Mesothelioma. Issue 4 (April 2015) - Nasu, Masaki; Emi, Mitsuru; Pastorino, Sandra; Tanji, Mika; Powers, Amy; Luk, Hugh; Baumann, Francine; Zhang, Yu-an; Gazdar, Adi; Kanodia, Shreya; Tiirikainen, Maarit; Flores, Erin; et al.
Abstract : Background: Breast cancer 1-associated protein 1 (BAP1) is a nuclear deubiquitinase that regulates gene expression, transcription, DNA repair, and more. Several findings underscore the apparent driver role of BAP1 in malignant mesothelioma (MM). However, the reported frequency of somatic BAP1 mutations in MM varies considerably, a discrepancy that appeared related to either methodological or ethnical differences across various studies. Methods: To address this discrepancy, we carried out comprehensive genomic and immunohistochemical (IHC) analyses to detect somatic BAP1 gene alterations in 22 frozen MM biopsies from U.S. MM patients. Results: By combining Sanger sequencing, multiplex ligation-dependent probe amplification, copy number analysis, and cDNA sequencing, we found alteration of BAP1 in 14 of 22 biopsies (63.6%). No changes in methylation were observed. IHC revealed normal nuclear BAP1 staining in the eight MM containing wild-type BAP1, whereas no nuclear staining was detected in the 14 MM biopsies containing tumor cells with mutated BAP1 . Thus, IHC results were in agreement with those obtained by genomic analyses. We then extended IHC analysis to an independent cohort of 70 MM biopsies, of which there was insufficient material to perform molecular studies. IHC revealed loss of BAP1 nuclear staining in 47 of these 70 MM biopsies (67.1%). Conclusions: Our findings conclusively establish BAP1 as the most commonly mutated gene in MM, regardless of ethnic background or other clinical characteristics. Our data point to IHC as the most accessible and reliable technique to detect BAP1 status in MM biopsies.